Online Access for Marketing, 14th Edition - Roger Kerin; Steven Hartley (McGraw-Hill Higher Education (International), 2018)
Kerin/Hartley's Marketing 14th edition is the most robust Principles of Marketing solution available to meet the needs of a wide range of faculty. Marketing focuses on decision making through extended examples, cases, and videos involving real people making real marketing decisions. The author team's decades of combined experience in the higher education classroom continue to inform the title's innovative pedagogical approach. Marketing is known for its conversational writing style, ability to engage students through active learning techniques, and vivid descriptions of businesses, marketing professionals, and entrepreneurs in cases, exercises, and testimonials that help students personalize marketing and identify possible career interests. Powerful tools like Connect, SmartBook, and the regularly updated resources at www.kerinmarketing.com make this 14th edition of Marketing the best choice for instructors seeking a rigorous, comprehensive program with balanced coverage of traditional and contemporary concepts.